How lockdown measures, during COVID-19 pandemic, matter on psoriatic patient's perception: Study on 600 patients on biologic therapy. Issue 7 (July 2021) - Bernardini, N.; Skroza, N.; Spagnoli, A.; Marchesiello, A.; Balduzzi, V.; Tolino, E.; Mambrin, A.; Michelini, S.; Maddalena, P.; Volpe, S.; Proietti, I.; Vestri, A.; et al.
Abstract: Background: The outbreak of coronavirus disease-2019 (COVID-19) is a public health crisis of global proportion. In psoriatic patients treated with biologic agents, evidence is not yet available on susceptibility to infection with the novel SARS-CoV-2 coronavirus, and data about the perception of COVID-19 and its impact on these patients are lacking. Aims: The aim of this observational, spontaneous study was the evaluation of the impact of anti COVID-19 measures in "fragile population" such as patients with a chronic inflammatory disease. Thus, we evaluated the impact of perceived risk on quality of life of patients with moderate to severe psoriasis, in our outpatient clinic, and how their perceptions changed before and after the adoption of Covid-19 emergency measures following the Italian Ministerial Decree in March 9, 2020. Methods: Using a series of questions, our study surveyed adult patients with moderate to severe psoriasis receiving treatment with biologic agents (n = 591), before and after the adoption of COVID-19 emergency measures. Results: Most patients (97%) had been sufficiently informed by healthcare staff about COVID-19 spread. A significant change was observed in social activity reduction before and after the adoption of the measures (18% vs. 90% of patients; P < 0.0001). Similarly, patients were more likely to suspend ongoing therapy after the measures were adopted than before (87% vs. 34% of patients; P < 0.0001). Following the measures, older patients were significantly more inclined to suspend therapy and reduce social activities than younger patients. Conclusions: Government COVID-19 emergency measures further curtailed already reduced social activities in psoriatic patients, and led to a greater inclination to suspend biologic therapy, more so in older patients, despite there being no evidence to support this suspension. These vulnerable patients may need support from clinicians in order to maintain treatment adherence.